Effect of Chlorophyll Meter and Leaf Colour Chart Based Nitrogen Management on Grain N Uptake for Rice in Iran - VALYNEJAD*, M.; VASEGHI†, S.; FALLAH‡, V.M.; PAZIRA†, E.; FALLAH‡, A.; MOAMENI‡, A. (Asian Journal of Chemistry, 2009)
Over application of N in rice leads to low N recovery efficiency and risk of NO3 pollution of ground water. The chlorophyll meter also known as SPAD meter, is a simple, portable diagnostic tool for identifying crop N status. We used it to test need based N management approaches for rice (Oryza sativa L.) in two varieties on a clay loam texture in northern Iran. The overall objective is to develop optimal N-management for Neda and Shirudi. Two varieties were grown under eight treatments. Eight treatments included a zero-N control, chlorophyll meter 35, 37, 40, LCC 4 and 5. SPAD readings were taken weekly on the topmost fully expanded leaves. Grain yield, yield attributes, total N uptake and fertilizer - N use efficiency were measured in both varieties. Both LCC and SPAD can be used to improve N management for Neda and Shirudi, but the optimal SPAD threshold for determining the timing of N-application was 35 and 37 for Neda and Shirudi, respectively. LCC treatments indicated that N-management based on LCC shade 5 helped avoid over application of N to rice. Neda had higher grain yield than shirudi, but the difference in maximum grain yield among SPAD and LCC treatments was insignificant. The two varieties didn't show a clear difference in fertilizer-N use efficiency. It is suggested that when N-management technology such as real time N-management (SPAD and LCC) were used, would avoid to over application of N fertilizer by rice farmers.